PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII - Mandayanti, Ditri Wily (Departemen Matematika, 2023)
The purpose of this research was to conclude whether the ability to solve math problems using the Creative Problem Solving learning model is greater to the direct learning model. This is based on test results which show that class VIII students of SMPN 13 Kerinci are still constrained in mastering one of these mathematical competencies. The type of research is quasi experimental with The Nonequivalent Posttest-Only Control Group Design approach. The population is all students of class VIII SMP Negeri 13 Kerinci for the academic year 2022/2023 using a simple random sampling technique. The research tool is a test of the ability to solve mathematical problems and uses the average similarity test t-test where the data is homogeneous and normally distributed. The results obtained after the t test showed that P-Value = 0.018 or less than the confidence level of 0.05. These results prove that the Creative Problem Solving learning model in solving mathematical problems is greater to the direct learning model. Keywords– Creative Problem Solving, Quasi Experiment, Mathematical Problem Solving